Discontinuous bifurcation of FRCC with zero-thickness interface modeling - Caggiano, Antonio (2023)
In this work, firstly a fracture-based interface constitutive theory, aimed at simulating the cracking mechanisms of Fiber Reinforced Cementitious Composites (FRCCs), is presented. The discontinuous formulation assumes a hyperbolic maximum strength criterion in terms of normal and shear joint stresses. The latter are evaluated on each crack front to simulate the failure behavior of plain and FRCC systems. A non-associated plastic flow rule, in conjunction with a post-cracking softening law, is defined to complete the modeling approach. On the other hand, the use of the most-classical Mixture Theory is followed for taking into account the actions of fibers in concrete matrix. The bridging mechanisms between fibers and active cracks are defined in terms of fiber-to-concrete bond–slip rule and dowel effects. Secondly, a normalized Cracking Indicator (CI) for discrete crack is proposed in the spirit of Hill's indicator for loss of stability of inelastic continua, to effectively evaluate the most critical direction for further loading in terms of the resulting energy release and crack opening, while accounting for the fiber direction and content. After presenting the constitutive theory and, particularly, the novel concept of the CI, numerical analyses at constitutive level are performed to evaluate the evolution of the fracture energy, post-peak strength, and critical cracking directions under variable fiber contents. Different load scenarios are evaluated, and the numerical predictions are compared with experimental data.